(untitled) (Revista Educação, Artes e Inclusão, 2023)
This article ains to present and discuss a methodological path, the interview-photographic essay, which proposes an approximation between art, education and research, inserted in an still in progress research, whose scope is the use of contemplative photography in higher education in health, presented as an action in a public university, in the form of discipline offered to undergraduate and graduate students. Starting from the Oral History in composition with a photo essay, we intend to clarify the relevance of the methodology chosen for the field of education and for qualitative research, discussing how this process of telling-creating, which involves exercises of sensitivity and attention, contributes for more humanized health training and for the quality of life of the participants. We believe that this proposal, combining interview and photography, in a deep connection between researcher and collaborator, by putting “soul, eye and hand” to work on the same creation, enhances the narrative capacity, thus opening a large window for human experience.